On the Hot Workability of Ti-6Al-4V Based on Thermal Processing Maps and Artificial Neural Network Modeling - Uz, Murat Mert; Yapici, Guney Guven; Yoruc, Afife Binnaz Hazar; Aydogan, Cahit Sertac (SPRINGER, 2025)
For probing the hot workability of Ti-6Al-4V alloy, uniaxial tensile tests were carried out in the temperature range of 500-800 degrees C and at quasi-static strain rates. The effects of deformation temperature and strain rate on the flow behavior of Ti-6Al-4V were investigated. The flow behavior was modeled with the artificial neural network approach with the resulting correlation coefficient and average absolute relative error of 0.9997 and 2.90621%, respectively. The statistical evaluation results showed that the applied model could predict with very high reliability for the range of deformation parameters. The 3D thermal processing maps indicate that there are unsafe conditions at low temperature and high strain rates. In addition, in cases where the temperature is high and the strain rate is low, flow stability is observed and high-power distribution efficiency is determined. The validation of thermal processing maps was carried out by microstructural examinations and fractographic analysis. Overall, it is asserted that the temperature range of 700-800 degrees C and the strain rates of 0.01 and 0.001 s-1 are the optimized process parameters for hot forming of Ti-6Al-4V.
Keywords: artificial neural network; hot workability; material characterization; Ti-6Al-4V titanium alloy; 3D thermal processing maps; HIGH-TEMPERATURE DEFORMATION; AUSTENITIC STAINLESS-STEEL; TITANIUM-ALLOY; CONSTITUTIVE MODELS; ALUMINUM-ALLOY; ARRHENIUS-TYPE; PURE TITANIUM; FLOW-STRESS; BEHAVIOR; SHEET; Materials Science